Exploring Patient Satisfaction with Hospital Services Using SERVQUAL: A Case Study in Bandarlampung Municipality, Indonesia - Safitri, Dina; Siti Ambarwati, Dwi Asri (Journal of Business and Management Review, 2024)
Research Aims: The research of hospital quality service in Indonesia by using SERVQUAL is limited in the literature. This research aims to analyze the dimensions necessary for hospitals to enhance service quality to meet the standards expected by stakeholders, hospital management, government, the academic community, and patients. Design/methodology/approach: The research employs a survey method, distributing questionnaires to hospital patients as research tool. The study population comprises hospital users in Bandarlampung Municipality, with purposive sampling utilized for selection. Respondents were given the option to complete a questionnaire before leaving the hospital or online via email or WhatsApp for those discharged. Research Findings: The findings reveal that dimensions of hospital service quality, including infrastructure, administrative procedures, overall patient experience, and hospital social responsibility, significantly influence patient’s satisfaction in hospitals in Bandar Lampung. However, the quality of human resources and security procedures do not exhibit a significant impact on patient’s satisfaction. Theoretical Contribution/Originality: This research expands the application of the SERVQUAL model beyond its traditional domains by analyzing hospital service quality within the Indonesian context. The study identifies critical dimensions such as infrastructure, administrative procedures, overall patient experience, and hospital social responsibility as significant predictors of patient satisfaction. By understanding these challenges, context-specific strategies for enhancing service delivery can be developed. Keywords : hospital services, patient satisfaction, human resources